Differences in karyotype between two sympatric species of Gymnotus (Gymnotiformes: Gymnotidae) from the eastern amazon of Brazil - Milhomem, Susana Suely Rodrigues; Pieczarka, Julio Cesar; Crampton, William Gareth Richard; de Souza, Augusto Cesar Paes; Carvalho Jr, Jaime Ribeiro; Nagamachi, Cleusa Yoshiko (Zootaxa, 2007)
In this paper we describe the karyotypes of two sympatric species of Gymnotus from Marajó Island, Pará, in the Eastern Amazon basin of Brazil. One of these species, G. mamiraua, has not previously been identified from this area. Karyotype studies demonstrate that G. cf. carapo Linnaeus, has 2n=42 (30M/SM+12ST/A) and G. mamiraua Albert & Crampton, 2n=54 (50M/SM+4ST). The Nucleolar Organizer Region (NOR) was found in the distal region of the short arm of pair 20 in G. cf. carapo and in the interstitial region of pair 1 of G. mamiraua. Both species have centromeric constitutive heterochromatin (CH) in all chromosomes and some in interstitial or distal regions. In both species, 4´6-Diamidino-2- phenylindole (DAPI) staining has shown banding concordant with C-banding, whereas the Chromomycin A3 (CMA3) staining in both species agrees with the NOR location. The new data and review of cytogenetic data in Gymnotus presented here is concordant with a hypothesis that G. carapo is either a complex of populations, or a complex of morphologically similar cryptic species with distinct karyotypes. These taxa may be reproductively isolated by prezygotic reproductive isolation barriers (such as the structure of the Electric Organ Discharge), or by post-zygotic barriers (such as karyotypic formula). The understanding of the cytogenetic structure of G. carapo, combined with associated studies of signal diversity, will yield insight into the mechanisms underlying the origins and maintenance of high species diversity in Gymnotus.